Patriotism and Love of the Neighbor: A Kierkegaardian View of a Contested Virtue - Evans, C. Stephen (Religions, 2023)
Though patriotism has traditionally been considered a virtue, in many countries of the world today, the status of patriotism as a virtue has been challenged. Philosopher John Hare has recently defended patriotism as a virtue. Kierkegaard, with his suspicion of “the crowd” and attack on “Christendom” has sometimes been thought to be one of the critics of patriotism. This paper argues that Kierkegaard’s view is actually close to Hare’s. Kierkegaard does believe that patriotism can be a virtue, though it is perhaps especially susceptible to distortion and corruption. Patriotism, like other natural forms of “preferential love”, must be infused with the love of the neighbor to be a genuine virtue.